# i think i have to simplify.... but the question just says:

(2y-3)^2

possible answers:

a.4y^2+9

b.4y^2-6y+9

c.4y^2-12y+9

d.4y^2+12y+9

## separate and multiply based on

FOIL

first

outer

inner

last

(2y-3)^2=

(2y-3)(2y-3) then use foil and multiply the first term, outer term, inner terms then last terms .

(2y-3)(2y-3)

first terms multiplied

2y*2y= 4y^2

outer terms multiplied

2y*(-3)=-6y

inner terms multiplied

(-2y)*3=-6y

last terms multiplied

(-3)*(-3)=9

Now combined FOIL (first outer inner and last terms )

4y^2-6y-6y+9= but now you can combine the -6y's so (-6y-6y=-12y)

and you get 4y^2-12y+9

## duplicate post

## inner terms multiplied

2y***(-3)**=-6y

it is the same as the outer terms multiplied (the negative was misplaced before)

## Oh..it was a duplicate?

Oh well I solved it Dr.Bob.=D

anyways..ha

## thank you...

## Your welcome =)

## To simplify the expression (2y-3)^2, we need to expand and simplify it. In this case, we have a binomial raised to the power of 2, which means we need to multiply the binomial by itself.

To do that, we use the formula (a+b)^2 = a^2 + 2ab + b^2, where a is the first term and b is the second term of the binomial.

In our case, a = 2y and b = -3. Now let's substitute these values into the formula:

(2y-3)^2 = (2y)^2 + 2(2y)(-3) + (-3)^2

Next, let's simplify each term:

(2y)^2 = 4y^2

2(2y)(-3) = -12y

(-3)^2 = 9

Now combine these simplified terms:

(2y-3)^2 = 4y^2 - 12y + 9

Therefore, the correct answer is option c. 4y^2 - 12y + 9.